Cerebellar Purkinje Cells Generate Highly Correlated Spontaneous Slow-Rate Fluctuations - Cao, Ying; Liu, Yu; Jaeger, Dieter; Heck, Detlef H. (Frontiers in Neural Circuits, 2017)
Cerebellar Purkinje cells (PC) fire action potentials at high, sustained rates. Changes in spike rate that last a few tens of milliseconds encode sensory and behavioral events. Here we investigated spontaneous fluctuations of PC simple spike rate at a slow time scale of the order of 1 second. Simultaneous recordings from pairs of PCs that were aligned either along the sagittal or transversal axis of the cerebellar cortex revealed that simple spike rate fluctuations at the 1 sec time scale were highly correlated. Each pair of PCs had either a predominantly positive or negative slow-rate correlation, with negative correlations observed only in PC pairs aligned along the transversal axis. Slow-rate correlations were independent of faster rate changes that were correlated with fluid licking behavior. Simultaneous recordings from PCs and cerebellar nuclear (CN) neurons showed that slow-rate fluctuations in PC and CN activity were also highly correlated, but their correlations continually alternated between periods of positive and negative correlation. The functional significance of this new aspect of cerebellar spike activity remains to be determined. Correlated slow-rate fluctuations seem too slow to be involved in the real-time control of ongoing behavior. However, slow-rate fluctuations of PCs converging on the same CN neuron are likely to modulate the excitability of the CN neuron, thus introduce a possible slow modulation of cerebellar output activity.